Influence of body weight unloading and support surface during walking of children with cerebral palsy - Melissa Leandro Celestino; Gabriela Lopes Gama; Gabryella Santos Cordeiro Longuinho; Meico Fugita; Ana Maria Forti Barela
Introduction Partial body weight support (BWS) systems have been employed for gait training of children with cerebral palsy (CP). Therefore, it would be important to analyze if the type of walking surface and the amount of body weight unloading over lower limbs change the way these children walk. Objectives Investigate the influence of walking surface and amount of body weight unloading on the spatial temporal characteristics during walking of children with CP. Materials and methods Seven children with spastic CP between four and eight years old and GMFCS (Gross Motor Function Classification System) between I and IV, were videotaped walking with 0%, 15% and 30% of BWS on both dynamic (treadmill) and static (ground level) surfaces. Walking spatial temporal variables were calculated. Results Children walked with similar velocity in all experimental conditions. While stance duration decreased as the percentage of BWS increased, no differences were found for stance and swing periods and cadence. Children walked with longer steps and strides and with faster strides on static surface compared to dynamic surface. Conclusion Children with CP presenting different levels of motor impairment presented some alterations in the spatial temporal walking parameters as they walked with body unloading. However, such alterations might be due mainly to the type of walking surface than the percentage of body weight unloading on lower limbs.